2020
DOI: 10.3390/ani10081280
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Immunohistochemical Examination of Lymphoproliferative Lesions Caused by Marek’s Disease Virus in Breeder Chickens

Abstract: Marek’s disease is widely controlled by vaccination programs; however, chickens are not totally protected, especially immediately after the vaccination when a strong challenge could interfere with the effectiveness of vaccination in the absence of proper biosecurity practice. This case report describes the occurrence of Marek’s disease (MD) observed in a breeder chicken flock reared southeast of Sicily. MD outbreak occurred from 32 to 47 weeks with an increase in weekly mortality rate (+0.4–0.6%). Overall, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…As depicted by our findings, the examined chickens suspected of being diseased displayed the enlargement of peripheral nerves, an ovary with a cauliflower-like appearance, as well as enlarged liver and kidneys with focal nodular lesions. These observations align with those documented in prior research ( Hassanin et al, 2013 ; Zhuang et al, 2015 ; Boodhoo et al, 2016 ; El-Kenawy et al, 2019 ; Stamilla et al, 2020 ; Ewies et al, 2021 ; Birhan et al, 2023 ). Notably, 31 of 36 (86%) clinical samples inoculated on CAM of 11-day-old SPF ECEs (REV-free), showed pock lesions, embryo dwarfism, a swollen greenish pale liver, and a pale appearance of the heart.…”
Section: Discussionsupporting
confidence: 91%
“…As depicted by our findings, the examined chickens suspected of being diseased displayed the enlargement of peripheral nerves, an ovary with a cauliflower-like appearance, as well as enlarged liver and kidneys with focal nodular lesions. These observations align with those documented in prior research ( Hassanin et al, 2013 ; Zhuang et al, 2015 ; Boodhoo et al, 2016 ; El-Kenawy et al, 2019 ; Stamilla et al, 2020 ; Ewies et al, 2021 ; Birhan et al, 2023 ). Notably, 31 of 36 (86%) clinical samples inoculated on CAM of 11-day-old SPF ECEs (REV-free), showed pock lesions, embryo dwarfism, a swollen greenish pale liver, and a pale appearance of the heart.…”
Section: Discussionsupporting
confidence: 91%
“…Clinical signs of infected birds are most commonly seen between 12 and 30 weeks of age [30], and MD outbreaks usually occur from 32 to 47 weeks of the production cycle [31], which matches the median age of sick birds of 31 weeks recorded in this study.…”
Section: Discussionsupporting
confidence: 81%
“…1) which were mainly elongated and small to medium-sized lymphoblasts and lymphocytes. Tumor compositions are similar between organs, but sometimes the involvement may vary (Stamilla et al 2020;Khan et al 2021). Wen et al (2018) reported the existence of Marek's disease virus in the nucleus of lymphoid tumor cells in the liver with the presence of Meg Protein.…”
Section: Marek's Diseasementioning
confidence: 99%
“…Marek's disease is a common avian infection in chicken flocks worldwide (Birhan et al 2021). The Herpes virus is an etiological agent which has three serotypes (Stamilla et al 2020). In chicken, Marek's disease virus (MDV) causes a variety of pathological signs and symptoms in poultry (Lopez et al 2019;Khan et al 2021).…”
Section: Introductionmentioning
confidence: 99%